Central Banking Lessons from the Crisis. (Policy Papers; Policy Paper ;, 2010)
The broader governance reform debate-which goes beyond quotas to issues such as engagement by high-level policymakers, Fund management selection, Board structure, rules and accountability-has not got very far in garnering a consensus at the Executive Board. This is the case even though, in political circles, including the IMFC, and in civil society, expectations are high that the institution will tackle reforms key to its long-term effectiveness and legitimacy. The impasse reflects many factors. Partly it is a matter of not being convinced that governance is nearly as important as quota shares, partly of disagreement over the specifics of various proposals, and partly of concern that the conflation of quotas with governance-the 'package approach'-risks delaying the pivotal quota rebalancing exercise, scheduled to be completed before January 2011. This paper lays out the main governance issues, while putting forward variants of reform proposals that might command broader support. It takes as given that, even if quota reform has its own logic and deadline, this does not preclude parallel consideration of-and possibly decisions on-governance reforms, which can help make the case to domestic and international audiences that a broader reform of the Fund is underway.